Blood sugar sex magik [compact disc] (Warner Bros., 1991)
With their 1991 album, the Red Hot Chili Peppers perfected their mix of rock, funk, and hip-hop. The album also has the hit singles Give It Away; Under the Bridge; and Breaking the Girl.